Multikulturalisme: Re-imagining Agama - Gadis Arivia (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
The foundation of multiculturalism, based on identities created from free choices, assumes that firstly, religion must be viewed as a cultural construct, a reality originating from various texts that seek to create new meanings and imaginations. In a society where multiculturalism is not embraced, the resulting form of society is communalism. Such a society prioritizes identity politics (identity recognition) over difference politics (pluralism recognition).